A Double Doubt: Neurotic Self and Agency in an Era of Shifting Ideology in Cuba - Russo, Concetta (Mediterranean Journal of Social Sciences, 2012)
The clashing of Cuba and the capitalist world economy has heralded a new beginning in Cubaâ€™s revolutionary historiography.This paper analyzes the psychotherapy as a way to reconceptualise subjectivity in this era of shifting ideology.My research has beencarried out in a Mental Health Community centre in La Habana (Cuba). Patients of this kind of Service are referred to as â€œneuroticsâ€,people who, even though without a severe mental disorder, need psychological support because in a difficult moment of their lives. In asituation where the patient is disoriented about his/her perception of the "state of things", psychiatrists and psychologists may becomethe patientâ€™s guide.Nevertheless, as the results of my ethnographic research suggest, psychiatrists and psychologists donâ€™t use theirrole to shape the psychiatric care into a form of governmentality. Instead, they use the therapy, and the ironic speech sometimesincluded in it, also to highlight the social contradictions that bring citizens to a neurotic behaviour.